1962
DOI: 10.1002/pol.1962.1206217427
|View full text |Cite
|
Sign up to set email alerts
|

Apparent nucleation of a crystal‐crystal transition in poly‐1‐butene

Abstract: In a previous paper we reported on the kinetics of crystallization and a crystal-crystal transition in poly-1-butene.1 (For earlier references, refer to this paper; also, note a recent publication by Zannetti et a1.2) In the absence of stresses and high pressures the two transformations ( a ) melt + modification 2 and ( 6 ) modification 2 + modification 1 were shown under optimal conditions to be fast (minutes) and slow (days), respectively. The unstable modification 2 is characterized by a fourfold helix simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

1964
1964
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Unlike the case of the supercooled liquid -> form 2 transformation , where evidence of heteroge neous initiation was clearly apparent, the type of initiation cannot be positively identified . Boor and l\1itchell [25] have observed th at th e addition of polypropylene 01' stearic acid accelerates the form 2 -> form 1 transformation. ThiR indicates that the process is subj ect to heterogeneous initiation.…”
Section: Form 2-7form 1 C Rystal-crysta L Transformationmentioning
confidence: 99%
“…Unlike the case of the supercooled liquid -> form 2 transformation , where evidence of heteroge neous initiation was clearly apparent, the type of initiation cannot be positively identified . Boor and l\1itchell [25] have observed th at th e addition of polypropylene 01' stearic acid accelerates the form 2 -> form 1 transformation. ThiR indicates that the process is subj ect to heterogeneous initiation.…”
Section: Form 2-7form 1 C Rystal-crysta L Transformationmentioning
confidence: 99%
“…Three crystalline modifications of isotactic poly-1-butene have been described. Two forms were recognized at an early date (1) and have been studied extensively (2)(3)(4)(5)(6)(7)(8). More recently, a third form has received considerable attention (3,6,9).…”
mentioning
confidence: 99%
“…More recently, a third form has received considerable attention (3,6,9). Form I, T, = 13O-14O0C., is spontaneously (3,4) produced from 11; the transformation is accelerated by pressure (3), mechanical deformation (3) or, above 15OC., by nucleating agents (5). Form 11, T, = 120-126OC., crystallizes from the melt (3,4).…”
mentioning
confidence: 99%
“…Research, for evaluation of the effect of the presence of a second component on the transition kinetics, employed low molecular weight compounds including biphenyl, stearic acid, dioctyl phthalate, or 1-naphtylacetamide, polymers, including isotactic polypropylene (iPP) or high-density polyethylene (HDPE), and nanofillers. 22,25,26 Blending of iPB-1 with iPP, for instance, was found to accelerate the rate of the transition from form II to form I crystals of iPB-1. 25 For pure iPB-1, at ambient temperature, full conversion of form II to form I was achieved after aging for at least 6 days, whereas in blends with 25 m% iPP, the transition was completed after 3 days.…”
Section: Introductionmentioning
confidence: 98%
“…On the other side, the kinetics of the crystal-form II to crystal-form I transformation is a function of the thermodynamic variables temperature and pressure/ deformation, 7,20 and depends additionally on the presence of additives, i.e., of a second component. 22 The phase transformation is possible between about 248 K, which is the glass transition temperature, and about 333 K. The maximum rate of transformation is observed near ambient temperature, between 293 and 313 K. 3 Quantitative calorimetric analysis of the transformation rate of a specific PB-1 with a molecular weight of 525,000 g mol 21 and a fraction of isotactic pentades of close to 83%, which initially was melt-crystallized at 323 K, revealed that the transformation at 293 K is completed after about 300 h. 3 Pressure and mechanical deformation, in general, increase the rate of phase transformation since the nucleation density within the crystals gets increased. Additives also were found to accelerate the transformation by providing surfaces which support the development of the stable form I structure of PB-1.…”
Section: Introductionmentioning
confidence: 99%